The occurence of two systems of measurements and its implications in the Philippine furniture industry - Yan, Patricia Ann C. (UP College of Home Economics, 2012)
The study sought to examine the occurrence of two systems of measurement, the modern metric and the English systems, in the local furniture industry and to determine the issues surrounding the used of these two systems. Quantitative and qualitative approaches were employed using the survey, interview, and observation methods. A stratified ramdom sampling was utilized for the survey, while a stratified purposive sampling was utilized for the interview. Participants included 26 survey respondents and 10 interview respondents who were employees from two furniture export companies that used measurements regularly. The measuring tools and equipment of the selected furniture export companies in Laguna were also observed. A survey questionnaire, an interview guide, and an observation checklist were the instruments of the study. Results of the study showed that the modern metric and English systems of measurement were employed alternately or simultaneously from design conceptualization to furniture production. The prevailing bases for selecting the systems of measurement to be used were distinct between the two selected companies. One company based their choice on clients'preference and request, while the other company employed modern metric system for accuracy and consistency. The study also showed that there were no dominant issues and no major problems in the occurrence of two systems of measurement primarily because after many years of experience, employees were already adept in using the two systems. Also, those who have received formal education were more vocal in identifying and addressing the issues in the occurrence of two systems of measurement, while those who learned the use of measurement only by experience were comfortable by following directions despite the use of two systems of measurement.